Pemberdayaan Siswa melalui Pelatihan Pembuatan Buket sebagai Upaya Menumbuhkan Jiwa Entrepreneur Sejak Dini - Masiah Masiah; Laras Firdaus; Siti Nurhidayati; Septiana Dwi Utami; Siti Rabiatul Adawiyah; Lalu Jaswandi; Nofisulastri Nofisulastri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity aimed to empower students through bouquet-making training in order to enhance creative skills, independence, and entrepreneurial interest from an early age. The program was implemented with 35 ninth-grade junior high school students and involved 3 accompanying teachers. The methods employed included demonstration, hands-on practice, intensive mentoring, and product evaluation. The outputs of the activity consisted of student-made bouquet products and a simple bouquet-making guide intended for further learning activities at school. The results showed that 90% of students were able to create bouquets independently with good quality, while several students demonstrated improved creativity through design variations and material combinations. Questionnaire responses indicated that 100% of participants were highly satisfied with the activity, and 80% expressed interest in continuing bouquet-making at home as a potential small-scale business opportunity. These findings suggest that creative, product-based skill training not only improves students’ technical competence and creativity but also effectively fosters entrepreneurial interest at an early stage.